Surrallés, Alexandre; Espinosa, Oscar; Jabin, David (eds.) Apus, chiefs and presidents. Amazonian indigenous State and policy in the Andean countries. IWGIA, IFEA, PUCP, 2016. - Campanera Reig, Mireia (2018)
Apus, chiefs and presidents ... constitutes several achievements. First, the dissemination of the work of the international research group APOCAMPO that strives to nurture the reflection on the confluence of politics, the indigenous, the State and the Amazon, drawing a lively, contemporary composition and criticism. Second, for contributing to look at cities as indigenous spaces. And finally, for thinking the juridical as a language of relationship and political interpellation between diverse and changing social agents, whether due to tensions between indigenous, or between indigenous and non-indigenous, or even by unequal dialogue - sometimes deaf - with the State .